The Effect Of Digital Accounting On Company Profitability Amid The Threat Of Recession - Nur Faiza Mas'udiyah; Novia Oktaviani Febrilia; Rizky Abdul Kharim (Brilliant International Journal Of Management And Tourism, 2023)
The article we made with the title "The Effect of Digital Accounting on Company Profitability Amid the Threat of Recession" purpose to find out how Digital Accounting affects company profitability amid the threat of recession. The research methodology we use is quantitative methodology by collecting secondary data which we then process into graphs to make it easier for readers to understand the contents of this article. In this article, it can be concluded that Digital Accounting has an important role in the profitability of companies amid the threat of recession because it can be time efficient, save costs, and a realtime reporting process. Thus, the company can continue to operate.